Recovery of zinc and lead from zinc plant residue - Turan, Mehmet Deniz; Altundoğan, Hamdi Soner; Tümen, Fikret (My University, 2004)
Zinc and lead recovery from zinc plant residue (ZPR) has been investigated. The residue is discarded as a cake from a Waelz kiln processing zinc–lead carbonate ores. The zinc plant residue containing 11.3% Zn, 24.6% Pb, and 8.3% Fe was blended with H2SO4 and subjected to a process comprising roasting, water leaching, and finally NaCl leaching. The effect of roasting and leaching parameters on the zinc recovery was first studied. About 86% Zn was recovered after roasting at 200 °C for 30 min with an equal weight ratio of H2SO4/ZPR followed by leaching at 25 °C for 60 min with a pulp density of 20% solids. For lead recovery, the residual solid after zinc extraction was subjected to NaCl leaching. At a pulp density of 20 g/L, about 89% Pb was dissolved in 200 g/L NaCl at 25 °C in 10 min.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Zinc; Lead; Leaching; Zinc plant residue; Sulphuric acid; NaCl